Kidney Cografts Enhance Fiber Outgrowth from Ventral Mesencephalic Grafts to the 6-Ohda–Lesioned Striatum, and Improve Behavioral Recovery - Ann-Charlotte Granholm; Stephanie Henry; Meleik A. Hebert; Servet Eken; Greg A. Gerhardt; Craig Van Horne (Cell Transplantation, 1998)
Recent studies have demonstrated the presence of many different neurotrophic factors in the developing and adult kidney. Due to its production of this mixture of neurotrophic factors, we wanted to investigate whether fetal kidney tissue could be beneficial for neuritic fiber growth and/or cell survival in intracranial transplants of fetal ventral mesencephalic tissue (VM). A retrograde lesion of nigral dopaminergic neurons was performed in adult Fischer 344 male rats by injecting 6-hydroxydopamine into the medial forebain. The animals were monitored for spontaneous locomotor activity in addition to apomorphine-induced rotations once a week. Four weeks following the lesion, animals were anesthetized and embryonic day 14 VM tissue from rat fetuses was implanted stereotaxically into the dorsal striatum. One group of animals received a cograft of kidney tissue from the same embryos in the same needle track. The animals were then monitored behaviorally for an additional 4 months. There was a significant improvement in both spontaneous locomotor activity (distance traveled) and apomorphine-induced rotations with both single VM grafts and VM–kidney cografts, with the VM–kidney double grafts enhancing the motor behaviors to a significantly greater degree. Tyrosine hydroxylase (TH) immunohistochemistry and image analysis revealed a significantly denser innervation of the host striatum from the VM–kidney cografts than from the single VM grafts. TH-positive neurons were also significantly larger in the cografts compared to the single VM grafts. In addition to the dense TH-immunoreactive innervation, the kidney portion of cografts contained a rich cholinergic innervation, as evidenced from antibodies against choline acetyltransferase (ChAT). The striatal cholinergic cell bodies surrounding the VM–kidney cografts were enlarged and had a slightly higher staining density for ChAT. Taken together, these data support the hypothesis that neurotrophic factors secreted from fetal kidney grafts stimulated both TH-positive neurons in the VM cografts and cholinergic neurons in the host striatum. Thus, these factors may be combined for treatment of degenerative diseases involving both dopaminergic and cholinergic neurons.